H0LiCOW – V. New COSMOGRAIL time delays of HE 0435−1223: H0 to 3.8 per cent precision from strong lensing in a flat ΛCDM model. Issue 4 (22nd November 2016) - Bonvin, V.; Courbin, F.; Suyu, S. H.; Marshall, P. J.; Rusu, C. E.; Sluse, D.; Tewes, M.; Wong, K. C.; Collett, T.; Fassnacht, C. D.; Treu, T.; Auger, M. W.; et al.
Abstract: We present a new measurement of the Hubble Constant H 0 and other cosmological parameters based on the joint analysis of three multiply imaged quasar systems with measured gravitational time delays. First, we measure the time delay of HE 0435−1223 from 13-yr light curves obtained as part of the COSMOGRAIL project. Companion papers detail the modelling of the main deflectors and line-of-sight effects, and how these data are combined to determine the time-delay distance of HE 0435−1223. Crucially, the measurements are carried out blindly with respect to cosmological parameters in order to avoid confirmation bias. We then combine the time-delay distance of HE 0435−1223 with previous measurements from systems B1608+656 and RXJ1131−1231 to create a Time Delay Strong Lensing probe (TDSL). In flat Λ cold dark matter (ΛCDM) with free matter and energy density, we find H 0 =71.9^+2.4_-3.0 km s^-1 Mpc^-1 and Ω _Λ =0.62^+0.24_-0.35 . This measurement is completely independent of, and in agreement with, the local distance ladder measurements of H 0 . We explore more general cosmological models combining TDSL with other probes, illustrating its power to break degeneracies inherent to other methods. The joint constraints from TDSL and Planck are H 0 = 69.2_-2.2^+1.4 km s^-1 Mpc^-1, Ω _Λ =0.70_-0.01^+0.01 and Ω _k=0.003_-0.006^+0.004 in open ΛCDM and H 0 =79.0_-4.2^+4.4 km s^-1 Mpc^-1, Ω _de=0.77_-0.03^+0.02 and w=-1.38_-0.16^+0.14 in flat w CDM. In combination with Planck and baryon acoustic oscillation data, when relaxing the constraints on the numbers of relativistic species we find Neff = 3.34_-0.21^+0.21 in Neff ΛCDM and when relaxing the total mass of neutrinos we find Σmν ≤ 0.182 eV in mν ΛCDM. Finally, in an open w CDM in combination with Planck and cosmic microwave background lensing, we find H 0 =77.9_-4.2^+5.0 km s^-1 Mpc^-1, Ω _de=0.77_-0.03^+0.03, Ω _k=-0.003_-0.004^+0.004 and w=-1.37_-0.23^+0.18 .